2001
DOI: 10.1148/radiology.219.2.r01ma44484
|View full text |Cite
|
Sign up to set email alerts
|

Update of Breast MR Imaging Architectural Interpretation Model

Abstract: Additional investigation yielded a slightly modified model, but the diagnostic performance characteristics remain high, similar to those originally published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
1
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(123 citation statements)
references
References 19 publications
2
106
1
14
Order By: Relevance
“…They concluded that morphological criteria were useful features, but that standardization was also important. Other recent studies have confirmed that smooth or lobulated borders are architectural features that are highly predictive of benign disease (3,4).…”
mentioning
confidence: 86%
“…They concluded that morphological criteria were useful features, but that standardization was also important. Other recent studies have confirmed that smooth or lobulated borders are architectural features that are highly predictive of benign disease (3,4).…”
mentioning
confidence: 86%
“…Dynamic contrast-enhanced breast MR imaging (DCE-MRI) has been reported to have high sensitivity for cancer detection, reportedly as high as 88%-100%, but specificity may be relatively low as 68%-96% (4 -6,8,9). The high diagnostic value of the time-intensity curve (TIC) derived from DCE-MRI has been well documented in past studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Moreover, MR imaging has recently been used to analyze combined morphologic characteristics and kinetic enhancement patterns of breast lesions, and a combination of these parameters shows high positive predictive value (8,9).…”
mentioning
confidence: 98%
“…4,5,[21][22][23] Buadu and associates 9 reported diŠerent patterns of rim enhancement and concluded that early rim enhancement with progression to the center was fairly speciˆc for carcinomas. Matsubayashi's group 10 reported that whereas early Fig.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%